Trajectory tracking through the control of non-equilibrium Casimir force. (October 2022) - Iizuka, Hideo; Fan, Shanhui
Abstract : We consider systems consisting of multiple plates, where the dynamics of the positions and the temperatures of the plates is determined by the non-equilibrium Casimir forces and the heat transfer between them, respectively. We numerically and theoretically show that in these systems, the temporal dependence of the position of a plate can be made to conform to a prescribed trajectory through a feedback control scheme. We illustrate by simulations on both two-plate and three-plate systems. Our results indicate the significant potentials of using feedback control schemes to engineer the behaviors of mechanical systems governed by quantum and thermal fluctuations.